Kemampuan Penalaran Mahasiswa saat Memecahkan Masalah pada Mata Kuliah Telaah Kurikulum Matematika Sekolah Menengah - Saddam Al Aziz; Ali Azmar; Defri Ahmad; Fridgo Tasman; Ronal Rifandi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
This study aims to analyze the mathematical reasoning abilities of students in the mathematics education study program in the secondary school mathematics curriculum review course. This research was conducted by giving quiz questions in the form of descriptions to a class of students who were then analyzed the answers. The results of the student's answer analysis show that the students' mathematical reasoning ability is still low. The low level of students' mathematical reasoning skills in general lies in the ability of students to analyze problems, make conjectures, determine relationships between variables, and identify links between processes or concepts in a given case. So that many answers from students are not logical and wrong in concluding.